Fabrication of electrospun nanofiber catalysts and ammonia borane hydrogen release efficiency - Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In the present study, Electrospun nanofibers (Co-NF, Ni-NF, and Cu-NF) were used as efficient catalysts for hydrogen release through ammonia borane (NH3BH3) hydrolysis. Poly-(vinyl alcohol) solutions containing metal acetates provided sol gel materials for electrospinning. The electrospun fibers were fabricated by a low cost and facile technique. The effects of different process parameters such as solution preparation and electrospinning conditions that directly influence the texture, crystalline phase, and chemical properties of electrospun nanofibers fibers were studied. The nanofibers were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Brunauer Emmett Teller surface area (BET), and scanning electron microscope (SEM). The metal oxide loaded nanofibers with average diameters from approximately 187 to 452 nm showed catalytic activity toward increasing NH3BH3 hydrogen release efficacy, with activation energies as low as 41.59 kJ mol(-1) (Co-NF), 35.54 kJ mol(-1) (Ni-NF), and 36.70 kJ mol(-1) (Cu-NF). Based on recyclability tests, Co-NF metal oxide nanofiber catalysts showed unaltered catalytic activity toward hydrogen release and good chemical stability after ten successive cycles. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Ammonia borane; Electrospun; Nanofiber catalysts; CO-B; SODIUM-BOROHYDRIDE; CARBON NANOFIBERS; HYDROLYSIS; GENERATION; NANOPARTICLES; DEHYDROGENATION; TEMPERATURE; PRECURSOR; DIOXIDE; Chemistry; Electrochemistry; Energy & Fuels